STUDENTS AND TEACHER USE OF FACEBOOK: A LITERATURE REVIEW - Sukri Sukri; Elihami Elihami (JURNAL EDUKASI NONFORMAL, 2021)
The goal of this post is to go over some of the most recent research findings that have been released. The goal of this article is to analyze recent published research papers on students' and teachers' use of Facebook. The goal of the review is to offer a detailed account of the participants' Facebook usage profile or the amount to which users are involved in Facebook activities, rather than only discussing Facebook in relation to teaching or learning purposes or its educational value per se. The focus of this review will be on empirical facts rather than opinion or theoretical explanations on students' and teachers' use of Facebook. This review is divided into three sections that cover the major research topics: students' Facebook usage profile or extent of use, the effects of Facebook use and effects of Facebook use on student social presence and discussion, and effects of Facebook on students' academic performance), and students' attitudes toward Facebook. Overall, the findings imply that Facebook has had little educational utility, that students primarily use Facebook to keep in touch with known individuals, and that students are more likely to divulge personal information.